PROBLEMS AND SOLUTIONS IN TEACHING UZBEK AS A FOREIGN LANGUAGE - Avezova Anajon Ko‘paysin qizi (American Journals, 2024)
Challenges in teaching Uzbek as a second language have been discussed, and some solutions have been explained in this article. Moreover, the number of foreign students who are willing to learn how to speak in Uzbek, has been increasing in Tashkent. This encourages the development of teaching Uzbek as a second language.